ответ:207,6
Но лучше меня проверить потому что я думаю что это неправильно (смотря ты в каком классе)
Пошаговое объяснение:
1)211*672=141792
2)808-297=511
3)511-141281=-141281
4)-141281:98184=1,4 (округление 1,43894117167)
5)209-1,4=207,6
1)
sin(x)*sin(3x)
так как
sin (3x)= sin(2x + x) = sin(2x) cos(x) + sin(x)cos(2x), то
sin(x)*sin(3x)=sin(x)*[ sin(2x) cos(x) + sin(x)cos(2x)]=
=sin(x)*[2sin(x)cos(x)*cos(x)+sin(x)*(2cos^2(x)-1)]=
=sin^2(x)*[2cos^2(x)+2cos^2(x)-1]=sin^2(x)*[4cos^2(x)-1]=
=4sin^2(x)cos^2(x)-sin^2(x)
a. int(4sin^2(x)cos^2(x))dx=int(2sin(x)cos(x))^2dx=int(sin(2x)^2dx=
=int((1/2)*(1-cos(2*2x)))dx=(1/2)*(x-(1/4)*sin(4x))+c
б. int(sin^2(x))dx=(-1/2)int(1-cos(2x))dx=(-1/2)*[x-(1/2)sin(2x))]+c
итого
int sin(x)*sin(3x)dx=(1/2)*[x-(1/4)*sin(4x)]+c1+(-1/2)*[x-(1/2)sin(2x)]+c2=
=(1/2)*[(1/2)sin(2x)-(1/4)sin(4x)]+c
1)
sin(x)*sin(3x)
так как
sin (3x)= sin(2x + x) = sin(2x) cos(x) + sin(x)cos(2x), то
sin(x)*sin(3x)=sin(x)*[ sin(2x) cos(x) + sin(x)cos(2x)]=
=sin(x)*[2sin(x)cos(x)*cos(x)+sin(x)*(2cos^2(x)-1)]=
=sin^2(x)*[2cos^2(x)+2cos^2(x)-1]=sin^2(x)*[4cos^2(x)-1]=
=4sin^2(x)cos^2(x)-sin^2(x)
a. int(4sin^2(x)cos^2(x))dx=int(2sin(x)cos(x))^2dx=int(sin(2x)^2dx=
=int((1/2)*(1-cos(2*2x)))dx=(1/2)*(x-(1/4)*sin(4x))+c
б. int(sin^2(x))dx=(-1/2)int(1-cos(2x))dx=(-1/2)*[x-(1/2)sin(2x))]+c
итого
int sin(x)*sin(3x)dx=(1/2)*[x-(1/4)*sin(4x)]+c1+(-1/2)*[x-(1/2)sin(2x)]+c2=
=(1/2)*[(1/2)sin(2x)-(1/4)sin(4x)]+c
207,6 если нужно пошагово то напиши